“LAYLI VA MAJNUN” DOSTONI QORAQALPOQCHA TARJIMASI - Azilova, Z.G. (SCIENCE and SOCIETY, 2024)
In this article the translation of the A.Navoi epic “Layli and Majnun” into Karakalpak was analyzed in comparison with the original text. The number of verses are discussed in the original and translated versions, as well as their thematic consistency, and poetic artistry.